Comparative Physiological and Transcriptome Analyses Reveal Mechanisms of Salicylic-Acid-Reduced Postharvest Ripening in ‘Hosui’ Pears (Pyrus pyrifolia Nakai) - Jing Zhang; Mengmeng Wen; Rong Dai; Xiao Liu; Chunlei Wang (Plants, 2023)
Postharvest ripening of sand pear fruit leads to quality deterioration, including changes in texture, flavor, and fruit color. Salicylic acid (SA), an important defense-related hormone, delays fruit ripening and maintains fruit quality, but the underling mechanism remains unclear. Herein, we evaluated the efficacy of SA in delaying the ripening process of Pyrus pyrifolia cv. ’Hosui’ pear fruit, as evidenced by the reduction in fruit weight loss, inhibition of firmness loss, cell wall degradation and soluble sugars, and retention of total phenols. Based on comparative transcriptomic data, a total of 3837 and 1387 differentially expressed genes (DEGs) were identified during room-temperature storage of control fruit and between SA-treated and control fruit, respectively. Further KEGG analysis revealed that the DEGs were mainly implicated in plant hormone signal transduction, starch and sugar metabolism, and cell wall modification. Moreover, exogenous SA treatment also altered the expression of many transcription factor (TF) families, including those in the ethylene-responsive factor (ERF), NAM, ATAF, CUC (NAC), basic helix-loop-helix (bHLH), basic leucine zipper (bZIP), and v-myb avian myeloblastosis viral oncogene homolog (MYB) families. Together, the results offer important insights into the role of SA-responsive genes in controlling fruit ripening in sand pears.